1987
DOI: 10.1021/ac00147a015
|View full text |Cite
|
Sign up to set email alerts
|

Three-component self-modeling technique applied to luminescence spectra

Abstract: It Is shown that the selection of pure component spectral coefficients Is Improved when additional applicable constraints are Imposed. The method Is demonstrated first for a twocomponent system (the phosphorescence and delayed fluorescence of benzophenone) and then extended to three components. It Is first shown that It succeeds In reproducing theoretical curves used to construct an artificial three-component Input matrix and then It Is applied to resolve experimental spectra composed of the fluorescence of tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0

Year Published

1990
1990
2009
2009

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 22 publications
2
34
0
Order By: Relevance
“…Sun et al applied a three-component version of Borgen and Kowalski's method in Reference 27 to produce the pure fluorescence spectra of two conformers and eliminate background emission due to Raman scattering. 31 Their method required at least two regions where the component spectra did not overlap. Experimental spectra were measured at varying concentrations of chloroform to take advantage of differential quenching of the conformers by chloroform.…”
Section: Extensions Of Lawton and Sylvestre's Methods To Three Componentsmentioning
confidence: 99%
“…Sun et al applied a three-component version of Borgen and Kowalski's method in Reference 27 to produce the pure fluorescence spectra of two conformers and eliminate background emission due to Raman scattering. 31 Their method required at least two regions where the component spectra did not overlap. Experimental spectra were measured at varying concentrations of chloroform to take advantage of differential quenching of the conformers by chloroform.…”
Section: Extensions Of Lawton and Sylvestre's Methods To Three Componentsmentioning
confidence: 99%
“…The next steps in the analysis follow the approaches outlined by Lawton and Sylvestre (1971), Malinowski and Howery (1980) and Sun et al (1987). The data matrix, S, is normalized such that for each value of n the sum over I yields unity.…”
Section: Principal Component Analysismentioning
confidence: 99%
“…PCA has found many applications in optical spectroscopy. PCA has been used for the analysis of UV/visible fluorescence data (Giana et al, 2003) and its usefulness has also been demonstrated for high-performance liquid chromatography (Sun, Sears, & Saltiel, 1987;Vandeginste, Essers, Bosman, Reijnen, & Kateman, 1985) and time-resolved Fourier transform infrared spectroscopy (Helm, Labischinski, Schallehn, & Naumann, 1991;Perkins et al, 2004).…”
Section: Introductionmentioning
confidence: 99%